Unusual presentation of Takayasu Arteritis during pregnancy mimicking peripartum cardiomyopathy - Pakeerathan, A.; Kumanan, T.; Pradeepan, J.; Tharmalingam, T.; Gerald, S. (Sri Lanka College of Internal Medicine, 2025)
Takayasu arteritis (TA) is a chronic inflammatory vasculitis affecting medium and large arteries predominantly in young women which can result in lethal complications. The pathology involves mononuclear cell infiltration and granulomatous inflammation in the arterial wall, arterial thickening, stenosis, occlusion and aneurysmal dilation. During the acute phase, patients may experience non-specific constitutional symptoms which can pose significant diagnostic dilemmas. Here we describe a 33-year-old woman who presented with generalised weakness, fatigue, and malaise who was treated for peripartum cardiomyopathy and subsequently suspected to have TA based on an incidental finding of circumferential wall thickening of the carotid arteries on an ultrasound scan of thyroid. An aortogram confirmed the characteristic features of TA. Prompt diagnosis and intervention are essential to prevent life-threatening complications of this relatively rare condition.
Keywords: Takayasu arteritis; Medium and large vessel vasculitis; Peripartum cardiomyopathy